Tailoring the Cavity of Hollow Polyelectrolyte Microgels. Issue 1 (18th November 2019) - Wypysek, Sarah K.; Scotti, Andrea; Alziyadi, Mohammed O.; Potemkin, Igor I.; Denton, Alan R.; Richtering, Walter
Abstract: The authors demonstrate how the size and structure of the cavity of hollow charged microgels may be controlled by varying pH and ionic strength. Hollow charged microgels based on N ‐isopropylacrylamide with ionizable co‐monomers (itaconic acid) combine advanced structure with enhanced responsiveness to external stimuli. Structural advantages accrue from the increased surface area provided by the extra internal surface. Extreme sensitivity to pH and ionic strength due to ionizable moieties in the polymer network differentiates these soft colloidal particles from their uncharged counterparts, which sustain a hollow structure only at cross‐link densities sufficiently high that stimuli sensitivity is reduced. Using small‐angle neutron and light scattering, increased swelling of the network in the charged state accompanied by an expanded internal cavity is observed. Upon addition of salt, the external fuzziness of the microgel surface diminishes while the internal fuzziness grows. These structural changes are interpreted via Poisson–Boltzmann theory in the cell model. Abstract : Hollow, anionic microgels are synthesized and their responsiveness to pH, temperature, and ionic strength is investigated. Significantly, enlargement of the solvent‐filled cavity as well as unequal swelling behavior of the internal and external surfaces of the microgel is elucidated via static light and small‐angle neutron scattering. The results are interpreted via Poisson–Boltzmann‐based computer simulations.